Long-time behavior of a nonlocal dispersal logistic model with seasonal succession - Zhenzhen Li; Binxiang Dai (Mathematics in Applied Sciences and Engineering, 2022)
This paper is devoted to a nonlocal dispersal logistic model with seasonal succession in one-dimensional bounded habitat, where the seasonal succession accounts for the effect of two different seasons. Firstly, we provide the persistence-extinction criterion for the species, which is different from that for local diffusion model. Then we show the asymptotic profile of the time-periodic positive solution as the species persists in long run.